Effect of Leaf Litter from Cistus ladanifer L. on the Germination and Growth of Accompanying Shrubland Species - Juan Carlos Alías Gallego; Jonás González Caro; Virginia Hinojal Campos; Natividad Chaves Lobón (Plants, 2020)
Most communities with the presence of Cistus ladanifer are characterised by the low richness of accompanying species, with C. ladanifer, in most cases, exceeding 70% of the coverage of woody species. This fact could be due to the allelopathic activity attributed to compounds present in the leaves of C. ladanifer, which may have a negative effect on the germination and growth of woody species that share its habitat. One of the possible ways of incorporating allelopathic compounds to the soil is the degradation of leaf litter. Therefore, the aim of this study was to determine how the presence of leaf litter from C. ladanifer affects accompanying species. Under controlled conditions, we analysed the effect of C. ladanifer leaf litter on the germination and growth of seedlings of five species that share their habitat with C. ladanifer (Retama sphaerocarpa, Cytisus multiflorus, Lavandula stoechas, Cistus salviifolius, and Cistus crispus). Additionally, the effect of leaf litter on the species itself, C. ladanifer, has been studied. The experiments were designed with different concentrations of leaf litter (UL) and leaf litter from which the compounds with allelopathic activity were extracted (WL). The results show that such effect greatly depends on the analysed species, with L. stoechas being the most negatively affected species. On the other hand, C. multiflorus and C. salviifolius were only negatively affected at the stage of seedling growth. The results reveal the involvement of leaf litter in the allelopathic activity attributed to C. ladanifer and that its presence has a negative influence on the germination and growth of accompanying woody species. This shows the need to delve into the potential relevance of allelopathy as an interaction that determines the composition, structure and dynamics of a community.